4(α-l-Rhamnosyloxy)-benzyl isothiocyanate, a bioactive phytochemical that attenuates secondary damage in an experimental model of spinal cord injury. Issue 1 (1st January 2015) - Giacoppo, Sabrina; Galuppo, Maria; De Nicola, Gina Rosalinda; Iori, Renato; Bramanti, Placido; Mazzon, Emanuela
Graphical abstract: Abstract: 4(α-l -Rhamnosyloxy)-benzyl isothiocyanate (glucomoringin isothiocyanate; GMG-ITC) is released from the precursor 4(α-l -rhamnosyloxy)-benzyl glucosinolate (glucomoringin; GMG) by myrosinase (β-thioglucoside glucohydrolase; E.C. 3.2.1.147) catalyzed hydrolysis. GMG is an uncommon member of the glucosinolate group as it presents a unique characteristic consisting in a second glycosidic residue within the side chain. It is a typical glucosinolate found in large amounts in the seeds of Moringa oleifera Lam., the most widely distributed plant of the Moringaceae family. GMG was purified from seed-cake of M. oleifera and was hydrolyzed by myrosinase at neutral pH in order to form the corresponding GMG-ITC. This bioactive phytochemical can play a key role in counteracting the inflammatory response connected to the oxidative-related mechanisms as well as in the control of the neuronal cell death process, preserving spinal cord tissues after injury in mice. Spinal cord trauma was induced in mice by the application of vascular clips (force of 24 g) for 1 min., via four-level T5–T8 after laminectomy. In particular, the purpose of this study was to investigate the dynamic changes occurring in the spinal cord after ip treatment with bioactive GMG-ITC produced 15 min before use from myrosinase-catalyzed hydrolysis of GMG (10 mg/kg body weight + 5 μl Myr mouse/day). The following parameters, such as histological damage, distribution of reticular fibers in connective tissue, nuclear factor (NF)-κB translocation and nuclear factor of kappa light polypeptide gene enhancer in B-cells inhibitor, alpha (IκB-α) degradation, expression of inducible Nitric Oxide Synthases (iNOS), as well as apoptosis, were evaluated. In conclusion, our results show a protective effect of bioactive GMG-ITC on the secondary damage, following spinal cord injury, through an antioxidant mechanism of neuroprotection. Therefore, the bioactive phytochemical GMG-ITC freshly produced before use by myrosinase-catalyzed hydrolysis of pure GMG, could prove to be useful in the treatment of spinal cord trauma.